Triboelectric-piezoelectric-electromagnetic hybrid nanogenerator for high-efficient vibration energy harvesting and self-powered wireless monitoring system. (January 2018) - He, Jian; Wen, Tao; Qian, Shuo; Zhang, Zengxing; Tian, Zhumei; Zhu, Jie; Mu, Jiliang; Hou, Xiaojuan; Geng, Wenping; Cho, Jundong; Han, Jianqiang; Chou, Xiujian; et al.
Abstract: Energy harvesting is a key technology for the self-powered mode of wireless sensor nods and mobile terminals. A large number of devices have been developed to convert mechanical energy into electrical energy. Whereas great efforts have been made to improve the output performance, problems like energy dissipation, device life and response range still need to be addressed. Herein, we report a hybridized triboelectric-piezoelectric-electromagnetic nanogenerator efficiently harvesting vibration energy. Three harvest modes are integrated into a single device, whose core component is a magnetic levitation structure. On the one hand, it presents higher sensitivity than conventional spring or cantilever designs due to low energy loss, which favors the tiny energy harvesting like the slapping desk vibration and the running car vibration. On the other hand, the mechanical fatigue or damage can be avoided by the special structure design. Under 20 Hz, triboelectric nanogenerator (TENG) can deliver a peak output power of 78.4 μW, while the top (EMG2) and the bottom (EMG1) electromagnetic generator can provide a peak output power of 36 mW and 38.4 mW, respectively. Piezoelectric generator located at top (PEG2) and bottom (PEG1) can contribute a peak output power of 122 mW and 105 mW, respectively. The capacitor charge measurement reveals that unit combination performance is remarkably stronger than individual performance, and the combination of TENG+EMG1+EMG2+PEG1+PEG2 has the highest energy harvesting capacity. Finally, this device has been integrated into a wireless sensor system. Results show that the wireless sensor system can be activated and transmit temperature and vibration signal to control computer. This work has a vital significance to the development and application of the internet of things. Graphical abstract: Highlights: An energy harvester based on magnetic levitation structure with three harvest modes is proposed. The high output performance of the hybridized nanogenerator is demonstrated. The dynamic response of device is analyzed. The device is integrated into a wireless sensor system, which pushes forward a significant step to the internet of things.